Instability of Happiness: Perspectives from Positive Psychology, Neurobiology, and Stoicism - Putri, Ni Komang Puspita Nadine Parisya (Pusat Riset dan Inovasi Nasional, 2026)
This study explores emotional instability and its impact on happiness, focusing on Positive Psychology, Neurobiology, and Stoicism. It aims to identify factors influencing instability of happiness, including stress, social support, and neurobiological dynamics. The research seeks to develop effective strategies to enhance emotional stability and long-term well-being, contributing to theories and practices for fostering enduring happiness in individuals and society. This study employs a qualitative approach, combining in-depth interviews and document analysis to explore emotional instability and strategies for lasting happiness. Nine participants from psychology, neurobiology, and Stoicism fields share personal experiences through narrative analysis, identifying patterns in happiness fluctuations. A comprehensive literature review enhances findings, ensuring validity, credibility, and a holistic understanding of factors influencing emotional well-being.Research reveals happiness is multifaceted, influenced by psychology, neurobiology, and philosophy. Factors like stress, personality, and social support impact emotional stability. Positive psychology emphasizes gratitude, mindfulness, and cognitive restructuring. Stoicism focuses on self-control, acceptance, and living virtuously. Neurobiology highlights the role of brain chemistry and lifestyle factors like diet and exercise. By integrating these perspectives, individuals can cultivate resilience, manage emotions, and enhance overall well-being.This research examines emotional instability and its impact on happiness, combining insights from Positive Psychology, Neurobiology, and Stoicism. Key factors include stress, neurochemical imbalances, and social support. Strategies such as emotional regulation, mindfulness, and resilience-building enhance stability. The study highlights the integration of ancient wisdom and modern science to foster enduring happiness and improve overall well-being.